Beyond brief counseling and therapy - Presbury, Jack H.
This practical text fully integrates theory and technique of brief counseling while presenting the relationship as the key to any successful intervention. All chapters include ideas and tools for brief counseling and case studies that take the reader step-by-step through the techniques of the first session and beyond. It is written to engage readers and invite them to participate in both self-exploration and discovery